Overview of Students’ Perceptions of Guidance and Counseling Teachers’ Performance Satisfaction - Nurussakinah Daulay, Dian Reka Bayu (JIV-Jurnal Ilmiah Visi, 2024)
The current performance of BK teachers provides significant benefits, including assisting students in problem-solving, nurturing their strengths, and social and emotional skills. Students’ perceptions of their performance are crucial in enhancing the quality of educational services. Student satisfaction results from services meeting their expectations. BK teachers’ job satisfaction occurs when they meet students’ and work environment expectations.Top of FormThis study aims to determine the perception of students regarding satisfaction with the performance of BK teachers. The subjects in this study were students of grades X, XI, and XII. From the Computer Network Engineering, Software Engineering, Light Vehicle Engineering departments, there were a total of 180 respondents. The method used in this study was descriptive statistical analysis. Data management was done using Microsoft Office Excel. The data management method for this descriptive statistical analysis was using a Likert scale. The results of this study cover 3 aspects: cognitive, affective, and psychomotor aspects. From these three aspects, the percentage of respondents in the category of very satisfied was 55%, satisfied 43.9%, fairly satisfied 1.1%, and unsatisfied 0%. Then, the highest percentage in each aspect was satisfaction, with 86.7% for the cognitive aspect, 88.9% for the affective aspect, and 67.8% for the psychomotor aspect.